Disruptors of the Hsp90/Aha1 complex that reduce tau aggregation: Nonhuman/Lead optimization studies. (7th December 2020) - Keegan, Bradley M; Koren, John; Blagg, Brian S.J.; ,
Abstract: Background: Aberrant aggregation of misfolded microtubule‐associated protein tau ( MAPT, tau) is a hallmark of Alzheimer's disease (AD) and other neurodegenerative tauopathies. Recently, the ATP‐dependent molecular chaperone family has been identified as a critical mediator of the pathogenic accumulation of misfolded tau. In particular, studies have demonstrated that inhibiting the ATPase activity of Hsp90 reduces pathological tau accumulation and promotes the clearance of tau via the proteosome. Method: The ATPase activity of Hsp90 is regulated through interactions with a number of co‐chaperones, which direct specific proteins for interaction with Hsp90. Our team recently discovered that one of these co‐chaperones, Aha1 ( AHSA1 ), dramatically increases the production of aggregated tau in vitro (ThT fluorescence assays) and in vivo (transgenic rTg4510 tau mice). Result: We identified several small molecules that disrupt Aha1/Hsp90 interactions in vitro and demonstrated that one of these compounds, KU‐177, ablates Aha1‐driven enhancement of Hsp90‐dependent tau aggregation. Conclusion: Using KU‐177 as a parent compound, we are developing small molecule disruptors of the Aha1/Hsp90 complex for the treatment of Alzheimer's disease and have developed assays to evaluate their efficacy.